Maqasid-Al-Shariah as a Strategic Management Lens for Digital Governance in Halal Value Chains - Irma Suryani Lubis; Muslim Marpaung (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study examines the integration of maqasid al-shariah and digital governance in halal value chains using a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework. Articles indexed in Scopus from 2020–2025 were analyzed to identify theoretical patterns and research gaps. The findings indicate that existing studies remain fragmented, with maqasid primarily treated as a normative concept and digital governance addressed mainly from technological or compliance perspectives. This research proposes an integrative conceptual model linking maqasid al-shariah, digital governance, stakeholder engagement, institutional legitimacy, strategic resources, and sustainability outcomes. The synthesis demonstrates that maqasid can function as a strategic governance framework, while digital governance operationalizes Islamic values through transparent and measurable practices. The study contributes theoretically by repositioning maqasid as a strategic management lens and practically by offering guidance for value-based digital transformation in the halal ecosystem. Overall, maqasid-based digital governance emerges as a new paradigm for building ethical, resilient, and sustainable halal value chains.